2016
DOI: 10.1371/journal.pone.0157346
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Simulations Based on Limited Quantitative Data: Understanding How Musculoskeletal Models Can Be Used to Predict Moment Arms and Guide Experimental Design

Abstract: The utility of biomechanical models and simulations to examine clinical problems is currently limited by the need for extensive amounts of experimental data describing how a given procedure or disease affects the musculoskeletal system. Methods capable of predicting how individual biomechanical parameters are altered by surgery are necessary for the efficient development of surgical simulations. In this study, we evaluate to what extent models based on limited amounts of quantitative data can be used to predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Despite this limitation, our results are important because they identify novel, biomechanically-driven hypotheses to be experimentally tested. We have previously demonstrated that hypotheses derived from theoretical simulations and limited quantitative data improved the design and analysis of biomechanical experiments (Nichols et al 2016). Such experiments can also simultaneously address issues associated with external validation of our models.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Despite this limitation, our results are important because they identify novel, biomechanically-driven hypotheses to be experimentally tested. We have previously demonstrated that hypotheses derived from theoretical simulations and limited quantitative data improved the design and analysis of biomechanical experiments (Nichols et al 2016). Such experiments can also simultaneously address issues associated with external validation of our models.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the nonimpaired thumb model (excluding the wrist) was validated by replicating cadaveric and in vivo data (see Wohlman and Murray 2013). The endpoint forces simulated with the SE4CF and PRC models have not been evaluated against similar data, despite being based on experimental data (Blankenhorn et al 2007; Nichols et al 2015; Nichols et al 2016; Nichols et al 2017). While many studies summarize clinical outcomes of these surgeries, studies that provide the scope and quantitative detail needed to validate our biomechanicalsimulationsdonotexist.Experimentalvalidationisalsoneededtoinformexpansion of the models to include finger kinematics, which were excluded from this study, as well as extrinsic finger muscles, which we represented as reserve torques.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given these experimental results, it has become accepted practice to predict isometric muscles properties when direct measurements cannot or have not been made. In humans, skeletal muscle architectural principles have been generalized to explain healthy and pathological movement (Arnold et al., 2010; Binder‐Markey et al., 2019; Halilaj et al., 2018; Melzner et al., 2022; Sartori et al., 2017), guide surgical procedures (Bolsterlee et al., 2013; Delp et al., 1990; Nichols et al., 2016), understand muscle design (Blemker & Delp, 2006; Hosseini Nasab et al., 2022; Kapelner et al., 2020; Tennler et al., 2022) and predict performance (Crotin et al., 2022; Heiderscheit et al., 2022; Sinclair et al., 2022). Despite the scores of predictions made for a number of cases, direct validation is rare, and it is thus critical that we pursue validation of the major assumptions made and used in these human models.…”
Section: Introductionmentioning
confidence: 99%